A map of representations of Use / s User / s of illegal drugs from semiotics Statements - Palazzolo, Fernando (Universidad Nacional de La Plata, 2018)
The aim of this paper is to describe, implement and evaluate the scope of the analytical method known as Statements Semiotics for the analysis of social representations, from interviews with actors involved in the phenomenon of illegal drugs. This time it made possible to establish a first conceptual map of how different actors (lawmakers, social activists, drug users and ex drug users, state workers on addictions, members of civil organizations) define use and users of illegal drugs, being identified two discursive formations that are in tension. Also shows clearly some tensions within each discursive formation, as well as correlations between the two formations, and contradictions or opacities in the discourse of the actors